A Graphical Pressure Sensor Array with Multilayered Structure Based on Graphene and Paper Substrate. Issue 2 (14th February 2022) - Ji, Chao; Zhang, Qiang; Li, Qiang; Pei, Zhen; Zhao, Dong; Yuan, Zhongyun; Wang, Jie; Cheng, Yongqiang; Zhang, Wendong; Sang, Shengbo
Abstract : Back Cover : In article number 2100643 by Shengbo Sang and co‐workers, a paper‐based sensing array with layered structure and high sensitivity is prepared by using a writing method which is applied to graphic pressure sensing and distance position detection. Because many scenarios require a safe distance to be maintained, particularly under the influence of COVID‐19, the writable paper‐based sensor array is used to realize graphical distance perception and give warnings.